2017
DOI: 10.1136/bmjqs-2017-007071
|View full text |Cite
|
Sign up to set email alerts
|

Is quality important to our patients? The relationship between surgical outcomes and patient satisfaction

Abstract: We found a significant association between patient satisfaction and both 30-day readmission and the occurrence of postoperative surgical complications. Given this association, further study is warranted to evaluate patient satisfaction as a healthcare quality indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…Our primary goal, the importance of which is supported in recent literature [22], is to identify the determinants of patients' perception of the experienced quality of health services (henceforth EQ), which are relevant for practical interventions. We focus on patients' perceived experience with four types of health institutions: family physicians, specialists, hospitals, and laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary goal, the importance of which is supported in recent literature [22], is to identify the determinants of patients' perception of the experienced quality of health services (henceforth EQ), which are relevant for practical interventions. We focus on patients' perceived experience with four types of health institutions: family physicians, specialists, hospitals, and laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that satis ed patients are more likely to better comply with providers' medical regimens and orders, to continue using medical care services and to cooperate or maintain relationship with speci c providers when compared to unsatis ed patients [8,[10][11][12]. Besides, associations have been found between patient satisfaction and outcomes, such as readmissions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A more general approach links the quality of health services to patient satisfaction. [11] Patients, expressing their views on the services they experienced, assess the quality of health care they received according to the degree of coverage of their expectations. [12] Thus, integrating the measurement of patient satisfaction into a quality assurance program improves the organization's climate, employee morale and helps to recognize the efforts made to meet the needs of patients.…”
Section: Introductionmentioning
confidence: 99%